Workshop Branding Packaging sebagai Upaya Strategi Pemasaran pada Produk UMKM Komunitas LADAZA - Octoviani, Aniza; Puspita, Afrida Sary; Fatwara, Medy Desma (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
LADAZA (Al Fazza Trading Stall) is an MSME community consisting of sellers and customers in the Depok area, West Java. This community was founded in May 2023 and consists of parents (mothers) from the Al-Fazza school which is under the auspices of the Al Fazza Foundation. MSMEs play an important role in the Indonesian economy, being a tool to support the economy, so that the government encourages the development of MSMEs in Indonesia. One of the obstacles to the increasing popularity of MSMEs is the large number of similar products being sold, so it is necessary for MSMEs to carry out branding so that their products are at the top of people's minds. Branding can be done in an effort to increase sales and marketing. One way to carry out branding is with branding packaging. Branding is done by designing, selecting and determining packaging that has distinctive characteristics compared to similar products. This service is carried out with the aim of providing training to the LADAZA community so that they can carry out branding on the products offered. By first providing material related to marketing theory, then packaging design, and the use of technology in creating packaging that can help branding their products, the participants were able to understand the importance of branding as a strategic effort in facing competition in the market.